EVALUASI EFEKTIVITAS KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PAI DI SMKN 2 DEPOK - Reni Puspita Sari; Arifatus Solihah; Sabaruddin, (Santhet (Jurnal Sejarah Pendidikan Dan Humaniora), 2024)
This article discusses the effectiveness of the independent learning curriculum in PAI subjects at SMKN 2 Depok. The purpose of this article is to provide an impact on changes to the Independent Learning curriculum at SMK N 2 Depok, and to evaluate the effectiveness of the Independent Learning curriculum in PAI subjects at SMKN 2 Depok. The method used in this article is a qualitative approach so that the data collected is in the form of words rather than numbers and library research. The evaluation results show that regular evaluation and selecting appropriate evaluation methods are very important in ensuring the effectiveness of the independent learning curriculum in PAI subjects in the learning process. This article provides recommendations and suggestions for increasing effectiveness in the learning process, especially in PAI subjects. It is hoped that this article can provide insight and guidance for teachers in implementing the independent learning curriculum. The main issues that will be discussed are 1) Compliance of implementation with the concept of Freedom to Learn 2) Impact of evaluation on student learning